Fortalecimiento de potencialidades ambientales mediante la aplicación de educación ambiental en la I.E N°00659 “Franciso Tejada Rojas” - Galarreta Aguilar, Luis Antonio (2013)
This applicative character research work called: potential environmental strengthening through the implementation of environmental education in the educational institution N°. 00659 "Francisco Rojas Tejada"- Moyobamba 2011, establishes an initial and final environmental diagnostic in the topics (water, soil, air, flora, fauna and solid waste) of the students ofthe "4er, 5th and 6th" ofthe primary level; as well asto strengthen the environmental potential as the start of the so lid waste segregation. This work focused on the implementation of environmental education to strengthen the environmental potential with the purpose to raise the knowledge of the students about environmental issues; to get to meet the objectives of this research methodology was used, techniques and materials characteristic of the regular basic education that helped in the process of teaching and learning in the themes developed in classrooms and on field trips. The study was conducted with 65 students: 22 students from 4th grade, 21 students of the 5th and 22 students from 6th grade of primary education in the educational institution N°. 00659 "Francisco Tejada Red" in the Moyobamba district. In the results of the present investigation was able to establish that, in the initial survey prior to the implementation of the environmental education to strengthen the environmental potential of the students of primary education to a scale of learning from O - 10 are located a 9.09% ofstudents in the 4th graders, 9.52% in grade 5, and 9.09% in the 6th grade; results that allowed them to learn about the themes to work with the students. Later in the final survey then to implement environmental education to strengthen the environmental potential of the students immersed in the research on a scale of learning from O - 10 was a 4.55% of students ofthe 4th graders, 9.52% of students in the 5th grade and 0% In the 6th grade, which indicates that the 6° degree there were no students disapproved (See Chapter Ill- Results); making a total of95.31 % students approved in the three sections, With regard to the knowledge of the subjects of water, soil, air, flora, fauna and sol id waste using educational materials that helped in the process of learning; result that lets me say the success of implementing environmental education in the educational institution. Results shown in the hypothesis test in this research of character applicative in which the knowledge of the students increased in the different themes developed within and outside the classroom. The implementation of envir.onmental education influences in the strengthening of environmental potential in the educational institution N°. 00659 "Francisco Rojas Tejada", 2011. Al so implement and strengthened the environmental potential of the segregation of the solid waste through the theoretical and practica} workshops in the Institution, as the end product was implemented with 4 containers of different colors with a sign each to be able to easily identify and classify the solid waste: professional, paper, and inorganic glass (see Picture N°. 01). Showing the same students that if you can generate income from the sale of the solid waste and in particular with the PET bottles collected in the educational institution. Key words: environmental education, solid waste segregatio